Antelope, Bison, Cougar - A National Park Wildlife Alphabet Book. - Medley, Steven P (Yosemite National Park, Ca : Yosemite Association, 2001)
This colorful alphabet book spotlights the wildlife to be found in America's national parks. Featuring wonderful watercolor paintings and pencil drawings of various animals and parks, the volume is full of fascinating facts for readers of all ages.
All Juvenile
Keywords: Wild life; Natural history--Yosemite; Alphabet books; Nature; Yosemite National Park; Wild life Yosemite